降级路网组合出行交通流分配模型与算法 = Traffic assignment model and algorithm with combined modes in a degradable transportation network - 孟梦 Meng, Meng (2015)
研究降级路网条件下的组合出行交通平衡问题。首先，基于出行者对降级路网的不同风险态度，将出行者分为三类：守时型，冒险型和平均型。其次，考虑小汽车出行和小汽车换乘地铁出行两种出行模式，分析降级路网条件下不同用户类的组合出行行为，建立相应的多用户变分不等式交通分配模型，讨论模型解的性质。最后，设计模型的求解算法，并通过算例说明模型和算法的有效性。算例结果表明：不同出行时间预算的出行者在降级路网中的路径选择行为存在较大差异，路网降级程度对出行者出行选择行为影响显著；随着道路通行能力的降低，出行者更倾向于选择组合出行模式。To study the effect of the degradable road network on travel decision and traffic assignment, firstly all travelers were categorized into three classes: risk-averse travelers, risk-prone travelers and risk-neutral travelers. Secondly, two travel modes including car trip and car-subway trip were considered in a multi-modal networks. A stochastic traffic equilibrium model was proposed by using the variational inequality theory, and the properties of the solution were discussed. Finally, an example was used to testify the validity of the model and the algorithm. The results show that the travel behavior varies greatly with different travel time budget; with the decrease of traffic capacity, travelers prefer to choose the combined modes.